Characteristics of cases hospitalized in a mental health and diseases hospital within the scope of article 432 of the Turkish Civil Code - Örüm, Mehmet Hamdi (Journal of Dependence, 2021)
Objective: The aim of this study was to investigate the sociodemographic and clinical characteristics of cases hospitalized in Elazığ Mental Health and Diseases Hospital (MHDH) within the scope of article 432 of the Turkish Civil Code (TCC 432). Method: The records of the cases hospitalized in Elazığ MHDH with the decision of TCC 432 were retrospectively analysed. Sociodemographic and clinical information of the cases were obtained from the hospital registry system. The Brief Psychiatric Rating Scale (BPRS) scores on admission and discharge were used. Results: The mean age of cases (n=101) was 32.79±9.63 years. There were 50 cases (50.5%) who actively used alcohol and/or drugs (16 cases with methamphetamine, 17 cases with mixed substance use). In 75 (74.3%) cases, family members applied for the TCC 432 decision themselves. Thirty-two (31.7%) cases were diagnosed with schizophrenia, 20 (19.8%) cases were diagnosed with bipolar disorder and 37 (36.6%) cases were diagnosed with substance use disorder. Conclusion: The most important finding of this study is the high number of cases (36.63%) with a diagnosis of substance use disorder hospitalized within the scope of the TCC 432 decision. Involuntary hospitalization of the cases to psychiatry departments will continue to be discussed ethically unless necessary steps are taken.